Dynamique paysagère du littoral kribien face aux pressions de l’agro industrielle et de l’urbanisation - Philippes Mbevo Fendoung (Éditions en environnement VertigO)
Landscape problematic concern many of disciplines : sociology, anthropology and geography, etc. It inspired writers who analyzed it following the disciplinary colorations. In geography, the landscape is convened to describe and understand spatial dynamics ; in this case, the coastal zones which, because of their situation, are at the center of multiple stakes and subject to important modifications. It shows a considerable fragilization of which the main actors are agro-industrial and urbanization. This is the case in Kribi. In the aftermath of independence, several agro-industrial plantations were created. This is the case of the Cameroonian Society of Palmeraie (Socapalm) in 1968, Hevea of Cameroon (Hevecam) in 1975. A strong and rapid population growth is in progress, closely related to major large industrial projects undertaken recently in this region (Deep water port of Kribi, the gas station, Pipeline Chad-Cameroon...). These developments bring about remarkable transformations of the landscape and the physiognomy of the original environment. The shoreline now alternates between natural ecosystems, agricultural development and other equipment. This work analyzes the dynamics of the Kribian littoral landscape in the light of the various developments underway. The methodology articulates three points : the processing of satellite images (Landsat 1984, 2000 and 2016), the analysis of sociological data, and mobility and their consequences on the Kribian coastline. Socio-economic surveys complement people's perception of their landscape as mutations. It appears that between 1984 and 2016, the Kribian littoral landscape experienced a strong dynamic that must be curbed. Faced with this situation, the State has set up a legal and institutional mechanism favorable to the protection of coastal areas with fragile ecology.